PENDAMPINGAN PEMASARAN KERAJINAN HOME INDUSTRI TAMPAH BERBASIS MEDIA SOSIAL DI PEKON GEMAH RIPAH - Wulandari Wulandari; Rian Bagas Prasetya Aji; Joni Joni (Jurnal PkM Pemberdayaan Masyarakat, 2023)
The development of arts in the Indonesian region shows fairly rapid development. This can be seen in terms of the quality produced by the craft of woven bamboo handicrafts. Even though tampah is manually made with human power and is still a home industry, many people are interested. Hopefully, this implementation can help marketing tampah bamboo using social media Facebook.